2014
DOI: 10.4088/jcp.14f09292
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal Anti-inflammatory Drugs and 5-HT3Serotonin Receptor Antagonists as Innovative Antipsychotic Augmentation Treatments for Schizophrenia

Abstract: Each month in his online column, Dr Andrade offers practical knowledge, ideas, and tips in psychopharmacology to JCP readers in psychiatric and general medical settings. Psychopharmacology, National Institute of Mental Health and Neurosciences, Bangalore, India (candrade@psychiatrist.com). Department of ABSTRACTAntipsychotic treatment is the mainstay in the management of schizophrenia. However, despite optimum use of antipsychotic drugs, many schizophrenia patients continue to exhibit residual positive, nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Ondansetron is a 5-HT 3 serotonin receptor antagonist used primarily to reduce nausea and vomiting associated with chemotherapy, radiotherapy, post-surgery, and pregnancy. Since 5-HT 3 blockade produces a weak inhibitory effect on dopaminergic neurotransmission [213], ondansetron has been tested in the treatment of schizophrenia [214], Tourette's disorder [215] tardive dyskinesia [216], alcoholism [217] (Johnson et al, 2011), and OCD [218]. Both uncontrolled and placebo-controlled studies showed that ondansetron was safe and effective in treating refractory OCD, both in monotherapy and added on SSRIs.…”
Section: Ondansetronmentioning
confidence: 99%
“…Ondansetron is a 5-HT 3 serotonin receptor antagonist used primarily to reduce nausea and vomiting associated with chemotherapy, radiotherapy, post-surgery, and pregnancy. Since 5-HT 3 blockade produces a weak inhibitory effect on dopaminergic neurotransmission [213], ondansetron has been tested in the treatment of schizophrenia [214], Tourette's disorder [215] tardive dyskinesia [216], alcoholism [217] (Johnson et al, 2011), and OCD [218]. Both uncontrolled and placebo-controlled studies showed that ondansetron was safe and effective in treating refractory OCD, both in monotherapy and added on SSRIs.…”
Section: Ondansetronmentioning
confidence: 99%
“…In support of a critical role of inflammation in psychiatric diseases, add-on treatments with antiinflammatory drugs have been tested in severe and treatment-resistant psychiatric patients [56][57][58][59][60][61][62][63][64] . For example, acetyl salicylic acid (Aspirin) which interrupts the immuno-inflammatory cascade by inhibiting cyclooxygenase (COX)-1 and COX-2 showed promising results as an add-on treatment of schizophrenia in comparison to treatment as usual 60,63 .…”
Section: Discussionmentioning
confidence: 99%
“…In structural similarity analyzes, similar targets were found between leflunomide and 5-HT antagonist drugs, and 5-HT antagonist drugs were among the molecules with the highest binding affinity to the DHODH enzyme among the 7900 molecules. It has been demonstrated by other studies that 5-HT antigonists cause suppression of cytokine release in immune cells by causing serotonin blocking 83,[85][86][87][88][89] . However these studies did not consider or tested for DHODH inhibition that may be on the main pathway to the anti-inflammatory affect.…”
Section: Drugbankmentioning
confidence: 94%